2023
DOI: 10.3390/ijms24021342
|View full text |Cite
|
Sign up to set email alerts
|

FISH Diagnostic Assessment of MDM2 Amplification in Liposarcoma: Potential Pitfalls and Troubleshooting Recommendations

Abstract: MDM2 amplification represents the leading oncogenic pathway and diagnostic hallmark of liposarcoma, whose assessment is based on Fluorescence In Situ Hybridization (FISH) analysis. Despite its diagnostic relevance, no univocal interpretation criteria regarding FISH assessments of MDM2 amplification have been established so far, leading to several different approaches and potential diagnostic misinterpretations. This study aims to address the most common issues and proposes troubleshooting guidelines for MDM2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…12,13 MDM2 amplification acts as an oncogenic role in several malignant tumors. 14 This is the first case report in which MDM2 amplification has been found in combined hepatocellular-cholangiocarcinoma. Thus, the pathogenic significance of MDM2 amplification in combined hepatocellular-cholangiocarcinoma has not been elucidated.…”
Section: Discussionmentioning
confidence: 79%
“…12,13 MDM2 amplification acts as an oncogenic role in several malignant tumors. 14 This is the first case report in which MDM2 amplification has been found in combined hepatocellular-cholangiocarcinoma. Thus, the pathogenic significance of MDM2 amplification in combined hepatocellular-cholangiocarcinoma has not been elucidated.…”
Section: Discussionmentioning
confidence: 79%
“…MDM2 , YAP1 and IGF1R , which could provide leads for targeted therapies [23]. Moreover, previous studies found that MDM2 was among the oncogenes most often amplified as circular ecDNA across cancer types [15, 36]. Not only did circular amplicons achieve higher CNs, also the oncogene expression was higher corrected for CN due to increased chromatin accessibility and possible enhancer rewiring [15].…”
Section: Discussionmentioning
confidence: 99%
“…FISH assessment was conducted in accordance with the MDM2 amplification patterns observed in human liposarcoma 22 . A MDM2/GMCL1 ratio higher than 2 was considered indicative of MDM2 amplification.…”
Section: Methodsmentioning
confidence: 99%